Business Environment and Labor Market Outcomes in Europe and Central Asia Countries - Lopez-Garcia, Paloma (World Bank, Washington, DC, 2012)
New firm entry has been fundamental for job creation in the transition economies. Hence, the urge to reform the framework in which firms operate. This paper aims to improve our understanding of the business environment of the Europe and Central Asia (ECA) countries, as well as to assess which of the institutions that shape it are most important for labor market performance. To achieve that aim, the author groups the institutions into those affecting firm entry and those affecting business survival and growth, and proceeds to construct indicators to summarize them. Next, she analyzes the impact of the business environment institutions on the employment generated by the private sector of the countries, proxied by the service employment rate. The regression analysis uses an unbalanced panel of 28 ECA countries over 14 years-from 1988 to 2002. Recent literature on the labor market performance of the OECD countries argues that what matters for employment is the interaction between institutions and shocks. Accordingly, the explanatory variables used in the regression are the interactions between the transition shock suffered by the ECA countries and each of the business environment institutions previously defined. The author finds that access to finance is the most important institution across all ECA countries. The development of the financial sector can explain about 40 percent of private employment creation in the European transition economies according to the model. On the other hand, the poor access to finance in Bulgaria, Croatia, and above all, Romania, is the main factor behind their poor development of the private sector. Market regulation (credit and labor regulation), start-up costs, and the tax burden are all found to significantly affect employment as well.